RAISING THE LEARNING EFFECTIVITY THROUGH THE USE OF EXPERIMENTS - HIBKÝ, Martin; KULFASOVÁ, Eva (Trends in education, 2008)
In this article we deal with the possibility of raising the learning effectivity through the integration experiments to the learning process in technical education. From the theoretical point of view we analyze ideal forms of use of this method in the learning process and its infulence on students learning.
Keywords: experiment; teaching; learning effectivity; technic; technical education